Ultrahigh discharge efficiency and improved energy density in polymer-based nanocomposite for high-temperature capacitors application. (March 2021) - Chen, Hanxi; Pan, Zhongbin; Wang, Weilin; Chen, Yuyun; Xing, Shuang; Cheng, Yu; Ding, Xiangping; Liu, Jinjun; Zhai, Jiwei; Yu, Jinhong
Abstract: Electrostatic capacitors with excellent energy storage capacity and great thermal stability have become the researching focus. However, high-energy–density electrostatic capacitors are restricted through insurmountable drawbacks of low charge–discharge efficiency under high temperature/voltage working conditions. Herein, polyetherimide (PEI) nanocomposite films contains with two-dimensional boron nitride nanosheets (h-BNNS) are fabricated by solution casting method. Consequently, h-BNNS/PEI nanocomposite films exhibit tremendously breakdown strength ( E b 700 MV/m), accompany with a record discharge efficiency ( η 93.6%) at room temperature with filler content of 4 vol%. The simulations and experiments results suggest that the h-BNNS loading into the PEI matrix could efficiently improve the high-temperature endurance. Particularly, the composites films exhibit superior comprehensive capacitive properties, e.g., discharged energy density of 3.43 J/cm 3 along with η of 90.1% under 500 MV/m and 150 °C. Therefore, these characteristics render our polymer film an ideal material candidate for high-performance dielectric applications at evaluated temperature.